Carbohydrate CuAAC click chemistry for therapy and diagnosis. (24th June 2016) - He, Xiao-Peng; Zeng, Ya-Li; Zang, Yi; Li, Jia; Field, Robert A.; Chen, Guo-Rong
Graphical abstract: We summarize the impressive progress since 2010 made in CuAAC-based carbohydrate click chemistry for therapy and diagnosis. Abstract: Carbohydrates are important as signaling molecules and for cellular recognition events, therefore offering scope for the development of carbohydrate-mimetic diagnostics and drug candidates. As a consequence, the construction of carbohydrate-based bioactive compounds and sensors has become an active research area. While the advent of click chemistry has greatly accelerated the progress of medicinal chemistry and chemical biology, recent literature has seen an extensive use of such approaches to construct functionally diverse carbohydrate derivatives. Here we summarize some of the progress, covering the period 2010 to mid-2015, in Cu I -catalyzed azide-alkyne 1, 3-dipolar cycloaddition CuAAC "click chemistry" of carbohydrate derivatives, in the context of potential therapeutic and diagnostic tool development.